Qualitative Analysis of Adrenaline Using UV-Visible Spectral Measurements - Gunasekaran, S.; Thilak Kumar, R.; Periyanayagasamy, V.; Raihana, M.P. (Asian Journal of Chemistry, 2016)
A systematic approach has been employed to study the variation in the absorption activity of lmax of adrenaline with varying concentrations. Adrenaline was stored under different storage conditions to check whether any degradation takes place. Further, the interaction of adrenaline with some trace elemental constituents such as iron and zinc ions is also studied.